Kanu kāgaḍo dahīntharuṃ laī gayo - Mahetā, Tāraka (Navabhārata Sāhitya Mandira, 2009)
Collection of stories on humorous themes
Short stories. - Reprint. Originally published: 1999. - Gujarati in Gujarati-Schr
Keywords: Humorous stories; Gujarati